Creating Inclusive Developers: Integrating Accessibility Education Through a Practical Learning Method - Silva, Alan T. A.; dos Santos, Suzane S.; Mota, Marcelle P. (Anais do Simpósio Brasileiro sobre Fatores Humanos em Sistemas Computacionais (IHC), 2025)
Introduction: Although essential, software accessibility is still absent from many higher education computing programs, leaving a gap in the training of professionals. While past research has proposed methods for its inclusion, these often do not provide the resources needed for use. Objective: This work aims to address this gap by proposing a practical, structured, and reproducible accessibility teaching method to facilitate the inclusion of accessibility in computing courses. Methodology or Steps: To address this, we present and evaluate an accessibility teaching method that combines Project-Based Learning and Design Thinking. The key contribution is that it provides all necessary materials for its implementation: lesson plans, activity guides, and slides. Results: Results from three applications with students and professors indicate increased awareness and understanding of accessibility and positive feedback. These findings suggest the method can foster empathy and practical skills, supporting the inclusion of accessibility in computing curricula.